2004
DOI: 10.1139/f04-111
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for limited larval dispersal in black rockfish (Sebastes melanops): implications for population structure and marine-reserve design

Abstract: Although dispersal distances of marine larvae influence gene flow and the establishment of population structure, few data on realized dispersal distances exist for marine species. We combined otolith microstructure and micro chemistry of black rockfish (Sebastes melanops) to assess their potential to provide relative estimates of larval dispersal distance. In 2001 and 2002 we measured trace elements at discrete otolith regions, representing the (i) egg/early-larval, (ii) pelagic larval, and (iii) late-larval/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…from the core, larval and juvenile regions (for a total of 324 replicate spots). The three replicates from the core were represented by three sequential pits (Miller & Shanks 2004;Patterson & Swearer 2007) vertically collected after having visually detected the core (Ruttenberg et al 2005(Ruttenberg et al , 2008. Each run generally consisted of 40 s acquisition: 10 s blank to correct for background, 10 s ablation resulting in a pit about 10 µm deep and 20 s for washout.…”
Section: Otolith Microchemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…from the core, larval and juvenile regions (for a total of 324 replicate spots). The three replicates from the core were represented by three sequential pits (Miller & Shanks 2004;Patterson & Swearer 2007) vertically collected after having visually detected the core (Ruttenberg et al 2005(Ruttenberg et al , 2008. Each run generally consisted of 40 s acquisition: 10 s blank to correct for background, 10 s ablation resulting in a pit about 10 µm deep and 20 s for washout.…”
Section: Otolith Microchemistrymentioning
confidence: 99%
“…core, larval and juvenile regions) can be used to discriminate among groups of juveniles that use different locations, environments or habitats (e.g. lagoons, estuaries, open marine waters) during their ontogenetic development (Campana 1999;Miller & Shanks 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This metric is much harder to estimate as it requires information about larval exchange among a network of populations. Few studies have tracked larval dispersal among populations (Miller and Shanks 2004;Becker et al 2007;Planes et al 2009;Shima and Swearer 2009); fewer still have empirically estimated temporal variation in dispersal (Miller and Shanks 2004); and none have empirically investigated the degree of temporal stability in connectivity among a network of populations.…”
Section: Introductionmentioning
confidence: 99%
“…For reef Wshes, ecological evidence has demonstrated that passive dispersal alone cannot explain larval distributions (e.g., Leis and Carson-Ewart, 1998). Several studies have focused on early life-history traits (e.g., Doherty et al, 1995) and larval behaviour (e.g., Marliave, 1986;Miller and Shanks, 2004;Neilson and Perry, 1990) and tried to correlate them to dispersal potential. It would be interesting to understand if a coast with the range (ca.…”
Section: Introductionmentioning
confidence: 99%